Blocking the IGF2BP1-promoted glucose metabolism of colon cancer cells via direct de-stabilizing mRNA of the LDHA enhances anticancer effects - Xiang-liang Zhang; Ke-jun Li; Jin-xin Feng; Gao-jie Liu; Yan-lin Feng (Elsevier, 2021)
Colorectal cancer (CRC) is a commonly diagnosed cancer with poor prognosis and high mortality rate. Hyperthermia (HT) is an adjunctive therapy to enhance the antitumor effects of traditional chemo- or radio- therapy. Here, we report that a cluster of essential regulator genes and speed-limit enzymes of glucose metabolism were significantly elevated under HT from a glucose metabolism PCR array analysis. Under low glucose supply or glucose metabolism inhibition, CRC cells displayed increased sensitivity to HT treatments. By transcript sequencing from the established HT resistant (HTR) colon cancer cell line LoVo HTR, we observed that IGF2BP1, an RNA-binding protein, was significantly upregulated in HTR cells compared with parental cells. Furthermore, LDHA mRNA was identified as an IGF2BP1 direct target. An RNA immunoprecipitation assay and RNA pull-down assay consistently illustrated IGF2BP1 specifically bonds to the 3' UTR of LDHA mRNA, leading to enhanced stability of LDHA mRNA. Finally, we demonstrated that inhibiting the IGF2BP1-promoted glycolysis sensitized colon cancer cells to HT treatment via both in vitro and in vivo experiments. Our findings suggest that targeting the IGF2BP1-LDHA-glycolysis pathway might be a promising therapeutic approach to enhance the anti-cancer effects of HT treatment.